THE INTERNATIONALIZATION OF AND THE DEPENDENCY OF INTERNATIONAL INFORMATION SYSTEMS IN THE THIRD WORLD NATIONS / L ’ INTERNATIONALISATION DES SYSTEMES INTERNATIONAUX D’ INFORMATION ET LA DEPENDANCE DES PAYS DU TIERS-MONDE - Houda, Fatima (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2022)
see pdf